2021
DOI: 10.5935/1984-0063.20200076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of six weeks high-intensity interval training and resistance training in adults with obesity and sleep related breathing disorders

Abstract: Introduction:The effects of high-intensity interval training (HIIT) combined with resistance training (RT) in adults with obesity and sleep-related breathing disorders (SRBDs) is limited.Objective: This study aimed to examine the effects of HIIT combined with RT on subjective sleep disorders in adults with obesity and SRBDs. Material and Methods: This study was a pre-and post-test design. Seventeen adults with obesity and SRBDs were recruited into the study. They received 24 minutes of HIIT and 30 minutes of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…20 However, these studies prescribed a centerbased exercise program tailored by the researchers, which was different from the present study. 19,20 The center-based training may have fewer confounding factors and be easier for the participants to follow the study protocol. However, the home-based AIT combined with RT in our study was safe, practical to follow in general, and especially feasible to prescribe to obese adults with SDB because none of the participants reported any serious events during exercise.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…20 However, these studies prescribed a centerbased exercise program tailored by the researchers, which was different from the present study. 19,20 The center-based training may have fewer confounding factors and be easier for the participants to follow the study protocol. However, the home-based AIT combined with RT in our study was safe, practical to follow in general, and especially feasible to prescribe to obese adults with SDB because none of the participants reported any serious events during exercise.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, the studies have investigated the effects of a HIIT program in obese adults with SDB. 19 20 These studies showed an improvement in sleep indices 19 and subjective sleep disorders. 20 However, these studies prescribed a center-based exercise program tailored by the researchers, which was different from the present study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations